Probiotics reduce self-reported symptoms of upper respiratory tract infection in overweight and obese adults: should we be considering probiotics during viral pandemics?. (1st January 2021) - Mullish, Benjamin H.; Marchesi, Julian R.; McDonald, Julie A.K.; Pass, Daniel A.; Masetti, Giulia; Michael, Daryn R.; Plummer, Sue; Jack, Alison A.; Davies, Thomas S.; Hughes, Timothy R.; Wang, Duolao
ABSTRACT: Gut microbiome manipulation to alter the gut-lung axis may potentially protect humans against respiratory infections, and clinical trials of probiotics show promise in this regard in healthy adults and children. However, comparable studies are lacking in overweight/obese people, who have increased risks in particular of viral upper respiratory tract infections (URTI). This Addendum further analyses our recent placebo-controlled trial of probiotics in overweight/obese people (focused initially on weight loss) to investigate the impact of probiotics upon the occurrence of URTI symptoms. As well as undergoing loss of weight and improvement in certain metabolic parameters, study participants taking probiotics experienced a 27% reduction in URTI symptoms versus control, with those ≥45 years or BMI ≥30 kg/m 2 experiencing greater reductions. This symptom reduction is apparent within 2 weeks of probiotic use. Gut microbiome diversity remained stable throughout the study in probiotic-treated participants. Our data provide support for further trials to assess the potential role of probiotics in preventing viral URTI (and possibly also COVID-19), particularly in overweight/obese people.